2016
DOI: 10.1002/jctb.5120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluid dynamic conditions on 2,3‐butanediol production by Raoultella terrigena in SBTR: oxygen transfer and uptake rates

Abstract: BACKGROUND The fluid dynamic conditions play a key role in the development and scaling‐up of bioprocesses. In aerobic cultures, oxygen is an essential substrate for microbial growth, production and culture maintenance; an effective gas–liquid transfer must be achieved. Changes in fluid dynamics due to stirrer speed can affect the culture negatively, causing hydrodynamic stress (increasing shear stress) or oxidative stress (by an increase of available oxygen in the liquid phase). RESULTS Under oxygen‐limiting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The dissolved oxygen concentration was set at 5% in all cases because it has been reported that 2,3-BD production with Raoultella sp. strains is efficient under oxygen limiting conditions [18]. Statistical analysis of variability associated to each factor indicated that glycerol concentration, temperature and cobalt-salt concentration significantly influenced the objective functions.…”
Section: Optimization Of Fermentation Conditions For the Wild-type Stmentioning
confidence: 96%
See 2 more Smart Citations
“…The dissolved oxygen concentration was set at 5% in all cases because it has been reported that 2,3-BD production with Raoultella sp. strains is efficient under oxygen limiting conditions [18]. Statistical analysis of variability associated to each factor indicated that glycerol concentration, temperature and cobalt-salt concentration significantly influenced the objective functions.…”
Section: Optimization Of Fermentation Conditions For the Wild-type Stmentioning
confidence: 96%
“…By increasing oxygen supply, higher cell densities and higher production rates are obtained. However, too much aeration, exceeding the microbial oxygen demand, leads to biomass and carbon dioxide as products [18]. Therefore, fine-tuning of oxygen availability is required in order to optimize 2,3-BD production, so the oxygen saturation was controlled at 5%.…”
Section: Characterization Of Fermentation Capacity Of the Mutant Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a stirred tank bioreactor (STBR), the airflow rate and the agitation are the main variables affecting fluid dynamic conditions, and they have a decisive importance in the growth rate of cells and in product distribution, even in the controlling step of the overall bioprocess rate culture . Many studies have shown how the agitation and aeration rates influence the oxygen transfer rate but there are much less studies on the influence on cell growth and metabolites productivity …”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Many studies have shown how the agitation and aeration rates influence the oxygen transfer rate but there are much less studies on the influence on cell growth and metabolites productivity. 4,[6][7][8] The biodesulfurization of fossil fuels has been widely studied, employing different biocatalysts to transform dibenzotiophene (DBT) into 2-hydroxybiphenil (2-HBP). 4,[9][10][11][12] This bioprocess has experienced a great impulse, since the 4S route had been discovered in Rhodococcus erythropolis IGTS68.…”
Section: Introductionmentioning
confidence: 99%